(untitled) (Revista Brasileira Multidisciplinar, 2009)
Based on an interdisciplinary view of the field of Science, Technology and Society (STS), we aim to understand the approaches to the Identity and Social Representation Theory in the Information Science field, by analyzing periodicals in this area. We evaluated scientific journals classified as Qualis A National, according to the CAPES concept, following pre-determined criteria. Once the articles were located, an analysis was performed, not only checking the theoretical approaches, but also considering the specificities, pluralities, dynamics and complexities of each approach. Eight articles were recovered. In relation to Identity, it is possible to verify that none of the identified articles was based on the same theoretical references that we have used (Ciampa). In relation to the theory of Social Representation, all the selected articles are in accordance with our theoretical approach (Moscovici). From the methodological point of view, a series of procedures were used, many of them reconsidering the interdisciplinary matter and the resulting advantages from interactions between areas. Qualitative nature research was the most used in the articles. Concerning data analysis, we emphasize the Lefévre and Lefévre Collective Subjective Discourse technique. The most used assessment tools were questionnaires and interviews. In this study it was possible to understand and reaffirm that these areas have much to contribute and add each other.